Amyloid-Like Aggregation in Native Protein and its Suppression in the Bio-Conjugated Counterpart - Mukhopadhyay, Anasua; Stoev, Iliya D.; King, David. A.; Sharma, Kamendra P.; Eiser, Erika (Frontiers in Physics, 2022)
Prevention of protein aggregation and thus stabilization of proteins has large biological and biotechnological implications. Here we introduce Dynamic Light Scattering (DLS) and DLS-based microrheology to show how native bovine serum albumin (nBSA) froms amyloid fibrils in weakly denaturing conditions as function of time, and how stoichiometric conjugation of BSA with polymer-surfactants (PSpBSA) protects the protein from such aggregation. Further, employing a combination of Thioflavin-T fluorescence, FTIR spectroscopy and other methods, we show that nBSA forms filamentous aggregates with amyloid-like structure, while PSpBSA proteins remain fully dispersed with only minor changes in their folding state, even when continuously heated for up to 5 days in denaturation conditions at 65 degrees C. Time-resolved DLS-based microrheology studies demonstrate that suspensions of the filamentous nBSA aggregates become viscoelastic for concentrations 200 µM. Our results indicate that after 6 days in aggregation conditions, the elastic modulus G´(omega) of nBSA solutions went from zero initially to values of up to 3.6 Pa, indicating that the filaments become long enough to form an entangled, viscoelastic network. Interestingly, heating 200 µM native BSA solutions at 65 degrees C for 2 days in Eppendorf tubes resulted in self-standing films rather than dispersed filaments. These films exhibited strong ThT-fluorescence intensities and a predominant alpha-sheet secondary structure in FTIR studies, suggesting that the self-standing microstructure of the film resulted from hierarchical self-assembly of the amyloid fibrils.